Development, Cross-Cultural Adaptation, and Psychometric Characteristics of the Persian Progressive Aphasia Language Scale in Patients With Primary Progressive Aphasia: A Pilot Study - Salime Jafari; Amin Modarresszadeh; Ahmad Reza Khatoonabadi; John Hodges; Noureddin Nakhostin Ansari; Cristian Leyton; Maryam Noroozian (Basic and Clinical Neuroscience, 2018)
Introduction: Primary Progressive Aphasia (PPA) is a neurological condition characterized by progressive dissolution of language capabilities. The Progressive Aphasia Language Scale (PALS) is an easy-to-apply bedside clinical scale capable of capturing and grading the key language features essential for the classification of PPA. The objective of the present study was to develop and validate the Persian version of the PALS (PALS-P) as a clinical language assessment test. Methods: In this cross-sectional study, PALS was translated and adapted into Persian according to the international guidelines. A total of 30 subjects (10 subjects with PPA and 20 control subjects without dementia) were recruited to evaluate the intra-rater reliability and discriminant validity of PALS-P. Results: The intra-rater reliability of the PALS-P within a 14-day interval was excellent for each subtest (ICC agreement range=0.81-1.0). PALS-P results were statistically significant among groups, suggesting its discriminative validity. Conclusion: This preliminary study indicates that PALS-P was successfully developed and translated. It seems to be a valid and reliable screening tool to assess language skills in Persian-speaking subjects with progressive aphasia.